10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
The shortened pre-clerkship phase in integrated medical curricula has raised concerns about whether medical students retain and apply foundational basic-science knowledge during clerkship. Yet few studies incorporate clerkship faculty perspectives, who directly observe students' mechanistic reasoning and are well-positioned to inform curricular interventions for vertical integration. This mixed-method study addresses that gap by conducting a clerkship faculty-centered needs assessment evaluating basic-science integration, students' preparedness, and priorities for physiology-focused electives during clerkship. Faculty overwhelmingly affirmed the importance of basic-science integration during clerkship (83%,). However, fewer than half believed the curriculum adequately achieves this. While 71% reported opportunities to assess students' application of basic-science knowledge during clerkship, only 53% felt students possessed adequate baseline knowledge. These findings suggest that integration on the wards is opportunistic, completely dependent on individual faculty initiative or clinical encounter, rather than deliberate curriculum design. Clerkship faculty identified renal/electrolyte physiology, pharmacology, and neuro-psychiatric physiology as potential high-yield elective topics for the elective course. Additionally, 79% of faculty agreed students would benefit from proposed fourth-year physiology electives, with the course on obesity pathophysiology receiving the highest number of first-choice rankings. Overall, the findings demonstrate a persistent gap in basic-science integration during clerkship and support the development of a clerkship faculty-informed, need-based physiology elective to reinforce mechanistic understanding and enhance receptivity among clinical educators, who cite time constraints and dense curricular expectations as major barriers to basic-science integration.